Repair products utilization: Suitability to stone materials and effectiveness control through time - Sánchez de Rojas, M. I.; García, N.; Frías, M. (Materiales de Construcción, 1995)
With the present study, the necessity of carrying out tests to select the most suitable restoration treatment is remarked. Showing how the results obtained evidence the products behaviour, although knowing and evaluating limitations due to laboratory tests, different to real conditions.